Pertumbuhan dan Hasil Bawang Merah (Allium ascalonicum L.) dalam Polybag Akibat Pemberian Pupuk KNO3 Berbagai Dosis - Jamaludin Jamaludin; Krisnarini Krisnarini; Rakhmiati Rakhmiati (Politeknik Negeri Lampung, 2021)
Shallots are one type of vegetable plant that has the potential to be cultivated in polybags to be used as filling plants in the yard of the house. The aim of the study was to determine the best dose of KNO3 fertilizer for the growth and yield of shallots in polybags. The treatments used in this study were unfertilized (0 g polybag-1), 0,3 g polybag-1, 0,6 g polybag-1, 0,9 g polybag-1, 1,2 g polybag-1, 1,5 g polybag-1, and 1., g polybag-1. The results showed that the treatment used had a significant effect on the growth and yield of shallots, especially on the variables of tuber diameter, dry bulb weight harvested per clump, and average dry weight harvested per tuber. KNO3 treatment dose of 0.9 g polybag-1 was the best treatment to increase the growth and yield of shallots in polybags